The Notary's Responsibility in Tax Avoidance Related to the Sale and Purchase Binding Agreement and Power of Attorney to Sell - Albi, Yuni; Saleh, Moh. (PT. Hafasy Dwi Nawasena, 2024)
This research discusses the responsibility of a notary in drafting a Sale and Purchase Binding Agreement (PPJB) with a Power of Attorney to Sell, which is suspected of involving tax avoidance. The aim of this study is to analyze the notary's responsibility in cases of tax avoidance carried out through the Sale and Purchase Binding Agreement and Power of Attorney to Sell made before a notary. Currently, there are no written regulations that explicitly prohibit or allow notaries to draft such agreements suspected of tax avoidance. However, notaries must act professionally and bear significant responsibility in performing their duties by adhering to the Notary Law (UUJN), the applicable code of ethics, and the prevailing legal regulations. A notary's work must be trustworthy, reliable, and aligned with Standard Operating Procedures (SOP), from the commencement of work to achieving accurate results. In addition to professionalism, a notary is also expected to provide proper and clear legal guidance to the parties involved. This study employs a descriptive-analytical approach with a normative juridical method. The research findings indicate that tax avoidance by a buyer in the drafting of a PPJB with a Power of Attorney to Sell is considered valid if neither the original seller nor the subsequent buyer files for the annulment of the PPJB or the Power of Attorney to Sell. Nevertheless, notaries are urged to exercise greater caution when dealing with clients who intentionally engage in tax avoidance, as such actions could have negative repercussions on the notary's reputation and legal standing.